CONSEQUENCES OF PUSH UP ON INSIDE THROWS OF FOOTBALL ATHLETES - Andreansyah, Ahmad Mico; Hardovi, Bahtiar Hari; Yono, Topo (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to find information about the effect of push ups on the results of throw-ins at SSB Putra Balung Jaya. The method used in this study is an experimental method to find a causal relationship (causal relationship) between two factors and the design of this study uses PreTest - Posttest Design. There are two variables in this study, namely push up training is an exercise that is carried out in a prone style with the hands as a support which strengthens the biceps and triceps muscles and the distance of the throw is the ability of SSB Balung Jaya players to throw the ball into the field with both hands as far as possible without initial movement until the ball touches the ground and is measured in meters. The population in this study were SSB Putra Balung Jaya players with a sample of 12 players, using a saturated sampling technique. The data collection technique used test and measurement techniques while data analysis was carried out using descriptive analysis techniques. The results of the descriptive test showed an average value in the pretest of throwing in 11.66 and an average value in the final posttest of throwing in training of 15.25. Looking at the results of the study, it can be concluded that push up training can affect the distance of throw-ins compared to before doing push up training.